1997
DOI: 10.1103/physreve.56.6970
|View full text |Cite
|
Sign up to set email alerts
|

Effect of shear flow on the stability of domains in two-dimensional phase-separating binary fluids

Abstract: We perform a linear stability analysis of extended domains in phase-separating fluids of equal viscosity, in two dimensions. Using the coupled Cahn-Hilliard and Stokes equations, we derive analytically the stability eigenvalues for long wavelength fluctuations. In the quiescent state we find an unstable varicose mode which corresponds to an instability towards coarsening. This mode is stabilized when an external shear flow is imposed on the fluid. The effect of the shear is seen to be qualitatively similar to … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…The goal of this paper is to explore the stabilization of cylindrical domains by an imposed shear flow. It is a sequel to my previous work on the stabilization by shear flow of a two-dimensional, lamellar domain in phaseseparating binary fluids [15]. In that paper it was shown that a lamellar domain at rest with diffuse interfaces is unstable towards a "varicose" instability.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…The goal of this paper is to explore the stabilization of cylindrical domains by an imposed shear flow. It is a sequel to my previous work on the stabilization by shear flow of a two-dimensional, lamellar domain in phaseseparating binary fluids [15]. In that paper it was shown that a lamellar domain at rest with diffuse interfaces is unstable towards a "varicose" instability.…”
Section: Introductionmentioning
confidence: 85%
“…consider a cylindrical domain in a solid binary alloy) a cylindrical domain in the two-phase state is still unstable. This is due to the Gibbs-Thomson effect, in which the chemical potential depends on the curvature [15,16]. The higher curvature at the necks will drive a diffusive flux towards the bulges, also leading to instability.…”
Section: Introductionmentioning
confidence: 99%
“…26 for an approximate concentration profile. Figure 2 shows the results of numerical simulation of Eq.…”
Section: Instability In the Absence Of Flowmentioning
confidence: 99%
“…26 We seek solutions of Eqs. ͑13͒ in the form of asymptotic series in powers of small wavenumbers k appropriate for the long-wave limit,…”
Section: ͑12͒mentioning
confidence: 99%
“…In [39][40][41], the thermodynamic stability of an equilibrium interface (also called a kink solution) was studied. It was found that such an interface is stable in respect to normal perturbations with the decay rate growing as k 3 .…”
Section: Introductionmentioning
confidence: 99%